Comorbidities, pain and fatigue in psoriatic arthritis, psoriasis and healthy controls: a clinical cohort study. (16th December 2020) - Ballegaard, Christine; Skougaard, Marie; Guldberg-Møller, Jørgen; Nissen, Christoffer V; Amris, Kirstine; Jørgensen, Tanja S; Dreyer, Lene; Kristensen, Lars E
Abstract: Objectives: To explore the prognostic value of pre-specified comorbidities on treatment outcomes in PsA, and to compare baseline data with cutaneous psoriasis without arthritis and healthy controls (HC). Methods: Patients initiating conventional synthetic/biological disease-modifying antirheumatic drugs were enrolled in this clinical observational cohort study, and data on comorbidities, and clinical and patient-reported outcomes were retrieved at baseline and after 4 months. Pearson's chi-squared tests were performed to investigate the prognostic value of pre-specified comorbidities and achievement of ACR20, DAPSA50 and MDA. Mann–Whitney U tests were used to compare OMERACT PsA Core Outcome Set (COS) measures at baseline and follow-up for the pre-specified comorbidities. Results: A total of 100 PsA patients were included at baseline. Statistically significantly fewer patients with obesity achieved DAPSA50 compared with patients without obesity ( P =0.035), and fewer patients with hypertension ( P =0.034) and Charlson Comorbidity Index (CCI) ≥1 ( P =0.027), respectively, achieved MDA compared with patients without these comorbidities. Patients with obesity, hypertension, widespread pain, and CCI ≥1 had significantly worse COS measures at follow-up compared with patients without these comorbidities. At baseline, patients with PsA had higher disease burden compared with patients with cutaneous psoriasis and HC, including higher pain ( P <0.001) and fatigue ( P <0.001) scores, and more widespread pain ( P =0.002). Conclusion: Obesity, hypertension and CCI ≥1 were prognostic factors for poorer treatment outcome rates in PsA. Pain and fatigue were more frequently reported among patients with PsA compared with patients with cutaneous psoriasis and HC. Trial registration: The Danish National Committee on Health Research Ethics: H-15009080; Data Protection Agency: 2012-58-0004; ClinicalTrials.gov: NCT02572700.